Pengaruh Pendekatan Pembelajaran Deep Learning terhadap Pemahaman Konsep Ipas Siswa Kelas Iv Sekolah Dasar - Salpina Dewi; Nurlaila Nurlaila; Samsul Bahri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to determine the effect of the deep learning learning approach on fourth-grade elementary school students’ understanding of IPAS concepts, particularly on the topic of pollination in perfect flowers. This research employed a quantitative approach with a quasi-experimental design using a pre-test and post-test control group design. The population consisted of all fourth-grade students of SDN 4 Muara Dua, totaling 58 students, who were divided into experimental and control classes through total sampling techniques. Data collection techniques included tests, observations, and documentation. The research instruments were tested for validity and reliability before being implemented in the study. The results revealed that the implementation of the deep learning approach had a positive effect on students’ understanding of IPAS concepts. This was indicated by the higher post-test scores achieved by students in the experimental class compared to those in the control class. In addition to improving conceptual understanding, the deep learning approach also enhanced students’ critical thinking skills, activeness, and participation during the learning process. Therefore, the deep learning learning approach can be considered an effective alternative strategy to improve elementary school students’ understanding of IPAS concepts.